Impacts of travel distance and travel direction on back-to-back games in the National Basketball Association - Charest, J.; Samuels, C. H.; Bastien, C. H.; Lawson, D.; Grandner, M. A. (Journal of Clinical Sleep Medicine, 2021)
Study Objectives: Travel fatigue and circadian disruptions are known factors that can hinder performance in professional athletes. The present study focused on travel distance and direction on back-to-back games over the 2013-2020 seasons in the National Basketball Association (NBA). Methods: The outcomes were based on winning percentage with additional covariates including the direction of travel (eastward or westward), the distance traveled (0-500km - 501-1000km - 1001-1500km - 1501km and more), team quality and season. If a team played both games of a back-to-back sequence on the road, they were considered Away-Away; if a team played the first game of a back-to-back sequence at home they were considered Home-Away; if a team played the first game of a back-to-back sequence on the road they were considered Away-Home. Results: The sequence Away-Home significantly increases the likelihood of winning compared to the Away-Away and Home-Away sequences: 54.4% (95%CI: 54.4,54.5); 39.2% (95%CI: 37.2,41.2), and 36.8%, (95%CI: 36.7,36.8), respectively. When teams travel back home, every additional 500km reduces the likelihood of winning by approximately 4% (p= 0.038). Finally, after withdrawing the Away-Home sequence, traveling eastward significantly increases the chance of winning (p= 0.024) compared to westward travel but has no significant impact on the probability of winning compared to neutral time zone travel (p= 0.091). Conclusions: The accumulation of travel fatigue and the chronic circadian desynchronization that occurs over the NBA season can acutely disturb sleep and recovery. It appears that tailored sleep and recovery strategies need to be dynamically developed throughout the season to overcome the different challenges of the NBA schedule.